LAPORAN POLISI PADA SENTRA PELAYANAN KEPOLISIAN TERPADU POLDA JAWA TENGAH BERBASIS WEB (Information Technology and Telematics, 2015)
Abstract-- Indonesian National Police as an instrument of state law enforcement, protector and guide the community has the authority to conduct criminal investigations, in order to make light of a case and find the culprit. As duty bearers of investigation, the police are required to improve professionally. In the investigation process, of course, begins with a report or complaint made formally by the competent authority set in legislation and made in written form, commonly called the police report.  With the Police Report On the Police Service Integrated Web-Based Central Java Police, is expected to provide more optimal services. Particularly with regard to legal certainty to the community in handling the case. Keywords : police report , case , Web-Based